Lithium‐Ion Batteries: 3D Interconnected Networks of Graphene and Flower‐Like Cobalt Oxide Microstructures with Improved Lithium Storage (Adv. Mater. Interfaces 1/2016). Issue 1 (January 2016) - Binitha, Gangaja; Ashish, Ajithan G.; Ramasubramonian, Deivanayagam; Manikandan, Palanisamy; Shaijumon, Manikoth M.
Abstract : In article number 1500419, M. M. Shaijumon and co‐workers fabricate a completely inter‐connected three dimensional reduced graphene oxide (rGO)–cobalt oxide composite material with unique flower‐like cobalt oxide microstructures uniformly embedded in a graphene hydrogel matrix (CoO‐GHG). The resulting synergistic improvement of porosity and conductivity of the composite material leads to significantly enhanced electrochemical performance as an anode for lithium‐ion batteries.